The factor that affecting fertilizer application effectiveness among smallholder in Felda Air Kangkong / Nurul Ulfah Ismail - Ismail, Nurul Ulfah (Faculty of Plantation and Agrotechnology, 2017)
In the plantation oil palm, fertilizer application is a major practice which can contribute to the profitability of the company. Currently, fertilizer application can be done by applied mechanically or manually at uniform rate without consideration to nutrient variably. The problem is excessive application of fertilizer lead to contaminate ground water, which people are not safe to drinking because it is raise to mineral content. The research was carried out to determine the factor that affecting fertilizer application effectiveness among smallholder. The data were analyzed in this survey are Reliability test, Descriptive analysis, ANOVA, Regression and Correlation with 87 sample out of 107 population. The result obtained from this study was method was significant difference since p-value is less than 0.05 which is 0.001.Through regression analysis was found that the most factors contributed to the fertilizer application effectiveness was method application with the value 0.229.The correlation analysis was found that only method application and skill have a positive relationship with production of yield since p-value is less than 0.05.The conclusion is method application as domain factor that affecting fertilizer application effectiveness.